A census of RND superfamily proteins in the Burkholderia genus. (July 2013) - Perrin, Elena; Fondi, Marco; Papaleo, Maria Cristiana; Maida, Isabel; Emiliani, Giovanni; Buroni, Silvia; Pasca, Maria Rosalia; Riccardi, Giovanna; Fani, Renato
Aim: The aim of this work was to analyze the eight resistance–nodulation–cell division (RND) families (a group of proteins mainly involved in multidrug resistance of Gram-negative bacteria) in 26 Burkholderia genomes in order to gain knowledge regarding their presence and distribution, to obtain a platform for future experimental tests aimed to identify new molecular targets to be used in antimicrobial therapy against Burkholderia species and to refine the annotation of RND-like sequences in these genomes.Materials & methods: A total of 417 coding sequences were retrieved and analyzed using different bioinformatics tools.Results & conclusion: A complex pattern of RND presence and distribution in the different Burkholderia species was disclosed and a core of proteins represented in all 26 genomes was identified. These 'core' proteins might represent useful targets of new synthetic antimicrobial compounds. Furthermore, the annotation of RND-like sequences in Burkholderia was refined.